De-institutionalisation of people with mental illness and intellectual disability : the family perspective - Kock, Elizabeth (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2009.